The profiles of dizzy patients in emergency department, hospital universiti sains malaysia (husm): a retrospective stud - Zainon, Nor Faezah (2017)
Dizziness is a general term that is used to describe spinning sensation, light-headedness, off-balance and postural instability. Dizziness is common complaint during healthcare visit in emergency department and outpatients clinic. Many patients are affected by dizziness as it reduces the quality of life by having an impact in their well being and work productivity. There are four types of dizziness which are vertigo, presyncope, disequilibrium and others. This retrospective study was carried out to study the profiles of dizziness patients in emergency department, HUSM for 3 months (June –August 2016) duration. The findings were obtained by reviewing the medical records of dizzy patients who came to emergency department HUSM, which will eventually be used as a preliminary data that would establish a better awareness and management in handling dizzy patients. We managed to acquire 106 patients that comprises of female gender, that was dominating the number of dizzy patients by 60 (57%) cases, compared to male with 46 (43%) cases.The subjects are from two races, which are Malay(96%) and Chinese (4%). The age group of 50 until 60 years old had the highest number of dizziness cases with the percentage of 35%. Vertigo has the highest percentage(63%), followed by presyncope(30%), disequilibrium(6%) and lastly, others(5%). The result also showed that both recent Upper Respiratory Tract Infection (URTI) and positional related was the most factor that aggravate dizziness. Majority of the dizzy patients did not experience falls by 74% from the overall subjects. In summary, this study is parallel with other research and a bigger sample size in the future would be better result.